Determining the Antibiofilm Efficacy of Oregano Gel in an Ex Vivo Model of Percutaneous Osseointegrated Implants - Jemi Ong; Rose Godfrey; Brad Isaacson; Paul Pasquina; Dustin Williams (Microorganisms, 2022)
Biofilm contamination is common in patients with percutaneous osseointegrated (OI) implants, leading to frequent infections, irritation, and discomfort. Reported infection rates soar up to 65% as the recalcitrant nature of biofilms complicates treatment. There is persistent need for therapies to manage biofilm burden. In response, we formulated and tested oregano essential oil in a topical gel as a potential biofilm management therapy. We developed an ex vivo system based on an established ovine OI implant model with Staphylococcus aureus ATCC 6538 biofilms as initial inocula. Gel was administered to the samples across a period of five days. Samples were quantified and colony forming unit (CFU) counts were compared against a positive control (initial bacterial inocula without treatment). Significant biofilm reduction was observed in samples treated with oregano gel compared to controls, demonstrating the potential of an oregano oil-based gel as a biofilm management therapy at the skin-implant interface of percutaneous OI implants.